BIOMARKER-BASED DETECTION OF EPITHELIAL OVARIAN CANCER: A SYSTEMATIC REVIEW OF HE4, CA-125, AND ROMA SCORE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epithelial ovarian cancer remains a leading cause of gynecological cancer mortality because many cases are diagnosed at an advanced stage. Early symptoms are often vague, and reliable population-level screening tools are lacking. Serum biomarkers, particularly cancer antigen 125 (CA-125) and human epididymis protein 4 (HE4), along with the Risk of Ovarian Malignancy Algorithm (ROMA), have been widely studied for detecting epithelial ovarian cancer and stratifying malignancy risk in women with adnexal masses. Objective: This systematic review aimed to evaluate the diagnostic performance and clinical utility of HE4, CA-125, and ROMA score in biomarker-based detection and risk assessment of epithelial ovarian cancer. Methods: A systematic search was conducted across PubMed/MEDLINE, Scopus, Web of Science, Cochrane Library, Google Scholar, and reference lists of relevant articles. Studies were included if they evaluated HE4, CA-125, ROMA, or combined biomarker strategies in women with suspected ovarian malignancy, pelvic masses, or adnexal masses and reported diagnostic accuracy outcomes. Data were extracted on study design, population, menopausal status, biomarker cutoffs, reference standard, sensitivity, specificity, area under the receiver operating characteristic curve, and major diagnostic conclusions. Methodological quality was assessed using QUADAS-2 domains. Results: The search identified 892 records. After removal of 214 duplicates, 678 records were screened. A total of 587 records were excluded after title and abstract screening. Ninety-one full-text articles were assessed for eligibility, and 67 were excluded. Finally, 24 studies were included in the systematic review. CA-125 showed useful sensitivity, particularly in advanced epithelial ovarian cancer, but had limited specificity in benign gynecological disorders and premenopausal women. HE4 generally demonstrated higher specificity than CA-125 and was less frequently elevated in benign conditions such as endometriosis. ROMA score improved overall risk stratification by combining HE4, CA-125, and menopausal status. However, diagnostic performance varied across studies due to heterogeneity in cutoff values, assay platforms, menopausal distribution, histological subtype, disease stage, renal function, and study setting. Conclusion: HE4 and ROMA score provide diagnostic advantages over CA-125 alone, particularly by improving specificity and supporting preoperative triage in women with adnexal masses. CA-125 remains clinically useful but is insufficient as a stand-alone early detection marker. None of the evaluated biomarker approaches is adequate as an independent screening tool for average-risk asymptomatic women. Biomarker interpretation should be integrated with clinical assessment, imaging findings, menopausal status, and histopathological confirmation.